Liquidity and stock returns: empirical test - Liu, Yiyang (2009)
This dissertation examines relationship between liquidity and stock returns from 1993 to 2008 in UK stock market. It uses bid-ask spread and turnover as proxy for measure liquidity in cross-sectional and time series regression respectively. Empirical result shows liquidity do not affect expected stock returns in both cross-sectional and time series regressions, even adds firm size and book-to-market ratio as controlling variables. Bid-ask spread, turnover and firm size do not have predictive power to predict returns; however, book-to-market ratio has strong negatively related with stock returns in cross-sectional analysis. Portfolios are formed by bid-ask spread and turnover respectively in time series regression. Moreover, the portfolios’ premium can be explained by CAPM risk.